We use cookies to personalise content and advertisements and to analyse access to our website. Furthermore, our partners for online advertising receive pseudonymised information about your use of our website. cookie policy and privacy policy.
 
+0  
 
0
198
2
avatar

How would one solve this? 

 

[(1+tan(x))/sin(x)]-sec(x)=csc(x) 

 May 25, 2018
 #1
avatar
+1

Verify the following identity:

(tan(x) + 1)/sin(x) - sec(x) = csc(x)

 

Put (tan(x) + 1)/sin(x) - sec(x) over the common denominator sin(x): (tan(x) + 1)/sin(x) - sec(x) = (1 - sec(x) sin(x) + tan(x))/sin(x):

(1 - sec(x) sin(x) + tan(x))/sin(x) = ^?csc(x)

 

Multiply both sides by sin(x):

1 - sec(x) sin(x) + tan(x) = ^?csc(x) sin(x)

 

Write cosecant as 1/sine, secant as 1/cosine and tangent as sine/cosine:

1 - 1/cos(x) sin(x) + sin(x)/cos(x) = ^?1/sin(x) sin(x)

 

1 - (1/cos(x)) sin(x) + (sin(x)/cos(x)) = 1:

1 = ^?(1/sin(x)) sin(x)

 

(1/sin(x)) sin(x) = 1:

1 = ^?1

 

The left hand side and right hand side are identical:

(identity has been verified)

 May 25, 2018
 #2
avatar+99604 
+1

(1 + tan x  )  / sin x  - sec  x = csc x

 

(1 + tan x) / sin x  -    1 / cos x

 

(1 + sin x / cos x) /  sin x  - 1 / cos x

 

1/sin x + sinx / [ cos x sin x]  - 1/cos x

 

1 / sin x  + sin x / [ cos x sin x ]  - sin x / [ sinx cos x]

 

1 / sin x  + sin x [ sin x cos x] -  sin x / [ sin x cos x ]

 

1 / sin x   =    csc x

 

 

cool cool cool

 May 25, 2018

15 Online Users

avatar
avatar
avatar